2001
DOI: 10.1523/jneurosci.21-21-08548.2001
|View full text |Cite
|
Sign up to set email alerts
|

Topographic-Specific Axon Branching Controlled by Ephrin-As Is the Critical Event in Retinotectal Map Development

Abstract: The retinotectal projection is the predominant model for studying molecular mechanisms controlling development of topographic axonal connections. Our analyses of topographic mapping of retinal ganglion cell (RGC) axons in chick optic tectum indicate that a primary role for guidance molecules is to regulate topographic branching along RGC axons, a process that imposes unique requirements on the molecular control of map development. We show that topographically appropriate connections are established exclusively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
222
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(229 citation statements)
references
References 48 publications
6
222
1
Order By: Relevance
“…Thus far, it has been difficult to demonstrate ephrin-A5 in back branching and arborization in vivo (10,11), although in vitro studies have suggested a role for ephrin-A family members (12). We tested a specific role of ephrin-A5 in limiting arborization in vivo by performing CALI of ephrin-A5 with late E12 embryos, the stage when arborization in deeper layers begins (23) but before activity-dependent refinement (13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, it has been difficult to demonstrate ephrin-A5 in back branching and arborization in vivo (10,11), although in vitro studies have suggested a role for ephrin-A family members (12). We tested a specific role of ephrin-A5 in limiting arborization in vivo by performing CALI of ephrin-A5 with late E12 embryos, the stage when arborization in deeper layers begins (23) but before activity-dependent refinement (13).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that topographic-specific arborization is the critical event in forming the retinotopic map (12). Genetic deletion studies demonstrated that ephrin-A2 and ephrin-A5 restrict initial axon outgrowth (9), but analyses of topographically specific arborization caused by changes of ephrin-A gradients in vivo had not been performed because of lack of appropriate approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stripe assay was also applied to investigate neurite outgrowth and guidance behavior related to neuronal regeneration [12][13][14][15] and branch formation 16 . Furthermore, the stripe assay has proven valuable in dissecting signaling cascades initiated downstream of axonal guidance receptors activated by ligands printed in a striped pattern [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies from Drescher et al (1995) identified a graded expression of ephrins (originally called repulsive axonal guidance signal or RAGS) in the optic tectum, and further work from this and other groups brought insight into their mechanism of action and intracellular cascades (see, for example, Nakamoto et al, 1996;Monschau et al, 1997;Yates et al, 2001;Hansen et al, 2004;Knoll and Drescher, 2004;Rashid et al, 2005). It is now generally accepted that in the retina and optic tectum, ephrins and Eph receptors can act as repulsive guidance cues distributed in opposing gradients.…”
Section: Ephrins Direct Thalamic Axons To Find Their Cortical Targetmentioning
confidence: 99%